The Office for National Statistics Longitudinal Study (1971-2021): the opportunities for longitudinal research on the England and Wales population - Sizer, Alison (International Journal of Population Data Science, 2026)
This paper introduces the Office for National Statistics Longitudinal Study (ONS-LS). It highlights linkage of the 2021 Census data, and research opportunities it offers to examine a range of new topics, and socio-economic and demographic changes taking place since the 2011 Census. The ONS-LS follows a sample of the England and Wales population from Census data longitudinally (1971-2021), linking administrative data (births, deaths, cancer registrations), with capacity for linkage of data at low level geographies. Members are selected based on four birthdays, providing a 1% representative sample of the population. The study is maintained as a continuous multi-cohort through addition of new births and immigrants with the same four birthdays (members leave through death or emigration). The main strength of the ONS-LS is its large sample size ( 1.3 million), allowing analysis of small areas and specific population groups. It has been used for a variety of research including on: Mode of transport to work. Socioeconomic inequality in place of death. Cancer diagnoses/mortality among ethnic minorities. Outcomes of cared for children. Linkage of 2021 Census data provides opportunities to examine: new topics in the 2021 Census (sexuality, veteran status). longitudinal transitions related to questions first included in 2011 (e.g., language, national identity, passports). changes occurring during the 2011-21 intercensal period when the EU referendum and “Brexit” occurred. Covid-19 pandemic.